Giant intrinsic electrocaloric effect in ferroelectrics by local structural engineering - Wu, Bo; Tao, Hong; Chen, Kui; Xing, Zhipeng; Wu, Yan-Qi; Thong, Hao-Cheng; Zhao, Lin; Zhao, Chunlin; Xu, Ze; Liu, Yi-Xuan; Yao, Fang-Zhou; Zhou, Tianhang; et al. (Nature communications, 2025)
The electrocaloric effect of ferroelectrics holds great promise for solid-state cooling, potentially replacing traditional vapor-compression refrigeration systems. However, achieving adequate electrocaloric cooling capacity at room temperature remains a formidable challenge due to the need for a high intrinsic electrocaloric effect. While barium titanate ceramic exhibits a pronounced electrocaloric effect near its Curie temperature, typical chemical modifications to enhance electrocaloric properties at room temperature often reduce this intrinsic electrocaloric effect. Herein, a structural design is introduced for barium titanate-based ceramics by incorporating isovalent cations. This leads to a well-ordered local structure that decreases the Curie temperature to room temperature while preserving a sharp phase transition, enabling a large dielectric constant and tunable polarization. This design achieves a remarkable electrocaloric strength of ~1.0 K·mm/kV, surpassing previous reports. Atomic-resolution structural analyses reveal that the presence of multiscale nanodomains (from ~10 nm to >100 nm), and the dipole polarization distribution with gradual dipole rotation enable rapid phase transition and facile polarization rotation, accounting for the giant electrocaloric response. This work provides a strategy for achieving a strong intrinsic electrocaloric effect in ferroelectrics near room temperature and offers key insights into the microstructure landscapes driving this enhanced electrocaloric effect. The authors introduce a structural design with a well-ordered local structure for barium titanate-based ceramics, which decreases Curie temperature while preserves a sharp phase transition, enabling tunable polarization, large dielectric constant and intrinsic electrocaloric effect near room temperature.